2019
DOI: 10.1111/nph.15958
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction in the arbuscular mycorrhizal symbiosis has consistent but small effects on the establishment of the fungal microbiota in Lotus japonicus

Abstract: Summary Most land plants establish mutualistic interactions with arbuscular mycorrhizal (AM) fungi. Intracellular accommodation of AM fungal symbionts remodels important host traits like root morphology and nutrient acquisition. How mycorrhizal colonization impacts plant microbiota is unclear. To understand the impact of AM symbiosis on fungal microbiota, ten Lotus japonicus mutants impaired at different stages of AM formation were grown in non‐sterile natural soil and their root‐associated fungal communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…Previously, a statistically significant small effect of the development of functional arbuscules on root fungal communities was observed in the legume Lotus japonicus, in which depletion of Glomeromycotina OTUs in roots resulted in increased abundance of Ascomycota fungal species e.g. belonging to the orders Hypocreales and Helotiales [42,43]. In these studies mutants affected in genes acting upstream of mycorrhiza-dependent Pi transport were explored.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…Previously, a statistically significant small effect of the development of functional arbuscules on root fungal communities was observed in the legume Lotus japonicus, in which depletion of Glomeromycotina OTUs in roots resulted in increased abundance of Ascomycota fungal species e.g. belonging to the orders Hypocreales and Helotiales [42,43]. In these studies mutants affected in genes acting upstream of mycorrhiza-dependent Pi transport were explored.…”
Section: Plos Onementioning
confidence: 99%
“…However, how maize mycorrhizal microbial community homeostasis is affected by functional AM symbiosis traits is elusive. Recent studies performed with mycorrhizal Lotus japonicus mutants disrupted in the common symbiosis signaling pathway (CSSP) or downstream processes showed that an almost complete depletion of Glomeromycotina taxa and impaired arbuscule formation in roots were accompanied by an enrichment of few Ascomycota fungi and shifts in bacterial communities under greenhouse conditions [42,43]. On the other hand, knocking out CSSP genes didn´t affect the life cycle of the growth-promoting basidiomycete fungus Piriformospora indica (also known as Serendipita indica) in L. japonicus nor did silencing of CCaMK affect bacterial or fungal communities in roots of field-grown Nicotiana attenuata [44,45].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that certain bacterial taxa exert beneficial and synergistic effects on AM symbiosis, acting as so-called ‘mycorrhiza helpers’ ( Frey-Klett et al, 2007 ; van der Heijden et al, 2016 ; Ferreira et al, 2020 ). In Lotus japonicus , disruption of the AM symbiosis impacts other members of the root-associated microbial community ( Xue et al, 2019 ). Characterization of the root microbiome of AMF-S and AMF-R families will provide insight into the interplay between AMF, the broader microbial community, and host response.…”
Section: Discussionmentioning
confidence: 99%
“…In the second article, Xue et al . () used Lotus japonicus mutants impaired at different stages of AM formation to investigate the role of the AM symbiosis pathway and AM fungi on the structure of root‐associated fungal communities. They found that roots of L. japonicus mutants perturbed in AM symbiosis largely lack AM fungi and assemble ‘abnormal’ fungal consortia when grown in natural soils.…”
Section: What Are Your Favourite New Phytologist Papers Of Recent Yeamentioning
confidence: 99%